Genesis 2–3 in Early Christian Tradition and 4QInstruction - Wold, Benjamin G. (Dead Sea discoveries, 2016)
Narratives about the Garden of Eden from Genesis 2–3 were popular among both early Jewish and Christian interpreters. More than other compositions found at Qumran, 4QInstruction gives sustained attention to these chapters of Genesis when offering instruction. Observations about how creation traditions are used in 4QInstruction provides the opportunity to assess the intense debates about the use of these chapters among both the so-called “proto-orthodox” and “gnostic” Christians of, especially, the second-century ce. These competing interpretations of Genesis 2–3 in early Christianities display continuities with 4QInstruction and these interpretive strands offer perspective on later readers, most notably Augustine of Hippo.